ChemInform Abstract: Oxindole as Starting Material in Organic Synthesis. Issue 19 (May 2015) - Ziarani, Ghodsi Mohammadi; Gholamzadeh, Parisa; Lashgari, Negar; Hajiabbasi, Parvin
Abstract Review: advances in the use of oxindole as starting material in the synthesis of various organic compounds and drugs; 128 refs.